2016
DOI: 10.1073/pnas.1607946113
|View full text |Cite
|
Sign up to set email alerts
|

Reading intervention with a growth mindset approach improves children’s skills

Abstract: Laboratory experiments have shown that parents who believe their child's abilities are fixed engage with their child in unconstructive, performance-oriented ways. We show that children of parents with such "fixed mindsets" have lower reading skills, even after controlling for the child's previous abilities and the parents' socioeconomic status. In a large-scale randomized field trial (N classrooms = 72; N children = 1,587) conducted by public authorities, parents receiving a reading intervention were told abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 19 publications
7
44
0
Order By: Relevance
“…who viewed ability as fixed. Andersen and Nielsen (2016) find similar results on test scores of an intervention targeting parents of primary school children in Denmark. In contrast to these positive results, one of the implementations studied in Yeager et al (2016b) found no effect on college enrolment of a growth-mindset intervention targeted at secondary school students.…”
Section: Growth Mindset Feedbacksupporting
confidence: 63%
See 1 more Smart Citation
“…who viewed ability as fixed. Andersen and Nielsen (2016) find similar results on test scores of an intervention targeting parents of primary school children in Denmark. In contrast to these positive results, one of the implementations studied in Yeager et al (2016b) found no effect on college enrolment of a growth-mindset intervention targeted at secondary school students.…”
Section: Growth Mindset Feedbacksupporting
confidence: 63%
“…According to this line of thinking, agents invest time, effort and money in education, which provides knowledge and characteristics enhancing productivity and, thus, lifetime earnings. Teachers and parents provide key inputs into the education production function and empirical studies have found positive effects of parent involvement (Andersen & Nielsen, 2016) as well as both short and long run effects of teachers (Jackson, Rockoff, & Staiger, 2014;Chetty et al, 2014) on student outcomes. Empirical evidence also suggests that the return to education may be sizable.…”
Section: Behavioural Barriers To Educational Attainmentmentioning
confidence: 99%
“…Understanding the mechanism behind the SES‐caregiver speech association has the potential to inform large‐scale early intervention programs (e.g., Providence Talks) and move the field closer to an individualized intervention approach. For example, Andersen and Nielsen [] conducted a reading intervention with an embedded growth mindset component that teaches parents they can make a difference in their child's development (a growth mindset is in contrast to a fixed mindset where intelligence is viewed as a fixed trait that cannot be changed). They found that children of parents with the highest fixedness beliefs at study entry had the largest growth in reading skills post‐intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanism behind the SES-caregiver speech association has the potential to inform large-scale early intervention programs (e.g., Providence Talks 1 ) and move the field closer to an individualized intervention approach. For example, Andersen and Nielsen [2016] conducted a reading intervention with an embedded growth mindset component that teaches parents they can Figure 2. Adult word count significantly mediates the association between maternal education and MSEL VDQ (panel A), after controlling for clinical data collection site, diagnostic group, and sex of the infant.…”
Section: Language Environment Variables Mediate the Association Betwementioning
confidence: 99%
“…As an example, a recent parent‐focused literacy intervention embedded a growth mindset component highlighting helpful ways parents could praise their second graders’ effort rather than their ability. The intervention had a large effect on parents’ and children's participation in the program and on children's skills, but the effect was even more pronounced for parents who initially endorsed more fixed mindsets about their children's abilities . Thus, having a fixed mindset does not preclude parents from interacting with their children in ways that promote learning, but these parents might benefit most from information highlighting the role they can play in promoting their children's language and literacy development.…”
Section: Implications For Intervention and Suggestions For Researchmentioning
confidence: 97%